(untitled) (Tanzania Medical Journal, 2009)
Background: Total serum IgE may be helpful in the diagnosis of atopic and certain diseases. However, the normal range is very wide and levels do not correlate well with symptoms. Objectives: This study determined the levels of IgE in Nigerians, so as to provide additional reasons for the wide normal range of IgE values. Methods: One hundred and eight healthy Nigerian children (2- 12 years of age) and one hundred and fifty-six healthy Nigerian adults (15-54 years of age) were selected for determination of serum IgE levels using ELISA method. The subjects were grouped by locality (urban or rural), age, sex and with or without helminthiasis. Results: The level of serum IgE ranged between 30 – 750 IU/ml. The level of serum IgE was significantly reduced in children compared with adults independent of sex and locality. The level of serum IgE was significantly reduced in urban children compared with rural children, and in children without helminthiasis compared with children having helminthiasis. Conclusion: Sex, urbanization and helminth infestations affect the level of serum IgE particularly in children, therefore IgE may not be helpful for diagnostic purposes in children Tanzania Medical Journal Vol. 23 (2) 2008: pp. 9-10